KARYA TARI TANDE’ SEBAGAI REPRESENTASI FENOMENA SAWER PADA KESENIAN TAYUB MADURA DI SUMENEP - Handayani, Sri Cicik; Alkaf, Mukhlas (Institut Seni Indonesia Surakarta, 2023)
This article discusses the Tande' dance piece created by Sri Cicik Handayani as a representation of the sawer phenomenon observed during research in Tanah Merah Village, Sumenep Regency. The sawer phenomenon, which was once a sacred part of the Tayub Madura art form, has now undergone a shift in meaning. Tayub, which was once believed to bring good fortune and ward off misfortune or danger, is now more commonly seen as mere entertainment. This reflects a change in the function and meaning of the tradition. In the Tande' piece, the researcher addresses this issue through a new choreographic approach that emphasizes the spirit of the Tandha’ woman, a female figure in the tradition, as well as the various problems arising from the sawer phenomenon in Tayub Madura. Additionally, this work is intriguing because it incorporates various elements beyond movement, such as symbols and values embedded in the local community, all of which are presented in the form of a performance art. This research not only focuses on describing the Tande' dance itself but also delves into the creative process undertaken by the researcher, who also acts as the creator and dancer in the work. Therefore, this research falls into the category of artistic research, where the process of creating the work is an integral part of the scientific study. To collect data, the researcher employed several methods, including observation, interviews, and documentation, all of which played a crucial role in understanding and formulating this work.